Determinabilidade, negociação e elaboração das cláusulas de preço contingente (earn-out) nas operações de compra e venda de participação societária ou de estabelecimento e análise de conflitos à luz do princípio da boa-fé objetiva - Alves, Daniel Rodrigues (2016)
This master’s dissertation aims at making a thorough, critical and careful analysis of the earn-out clause (contingent price) inserted in purchase and sale agreements of mergers and acquisitions transactions involving the purchase and sale of equity interest or company’s assets. Given the intrinsic characteristics of the earn-out and its great potential for litigation, there is a clear need to verify which key elements should be included in the wording of such clause widely used in the transactions carried out under Brazilian Law in order to meet its nature, its economic rationale and achieve its goals while minimizing at large the potential of future disputes between the contractors. It is expected to provide to the reader, business law operator, the essential elements for the rational drafting of the wording (leaving aside the mere translation of foreign clauses and importation to the contract under Brazilian Law) and, even more, to the counseling to be given to its clients on the functioning of such clause under Brazilian Law and on the measures that the clients must take to avoid unfavorable decisions in future disputes. All the above should influence the reader to inquire on the option of using the earn-out clause in transactions that it may assist, considering the particular characteristics of each party involved, the target company and the other negotiating circumstances. To achieve these goals, this dissertation seeks to first examine the determinability and the legal nature of the earn-out clause under Brazilian Law, specifically on the rules governing the contractual relationship between the parties. Then it will begin a detailed analysis of the earn-out clause, including its typical elements, its operation and the main items to be taken into account in the negotiation and drafting of its wording. Finally, a description of two specific litigation cases discussed and prosecuted by United States courts involving earn-out will be given, followed by an analysis of such cases under the perspective of the principle of objective good faith (boa-fé objetiva) established under the Brazilian legal system to verify whether the judges’ decisions would be the same if the decisions were to be issued in the light of such principle that governs Brazilian contractual relationships.